UMPSA TVET Campaign at Kuala Krau promotes inclusive education - Noraini, Yusoff (UMPSA, 2024)
KUALA KRAU, 11 October 2024 – The UMPSA@Kuala Krau TVET Travel Programme not only aims to highlight the benefits of TVET education but also seeks to engage the general public with the potential and opportunities offered in this field.